Bioequivalence study of two long-acting formulations of oxytetracycline following intramuscular administration in bovines - Mestorino, Olga Nora (2016)
The aim of this study was to evaluate the bioequivalence of two commercial long-acting formulations based on oxytetracycline (OTC) hydrochloride between the reference formulation (Terramycin LA, Pfizer) and a test formulation (Cyamicin LA, Fort Dodge Saude Animal). Both formulations were administered in a single intramuscular route at a dose of 20 mg OTC/kg of body weight in clinically healthy bovines. The study was carried out according to a one-period parallel design. Plasma samples were analyzed by high-pressure liquid chromatography. The limit of quantitation was 0.050 μg/mL with an accuracy of 101.67% with a coefficient of variation of 13.15%. Analysis of variance and 90% confidence interval tests were used to compare the bioavailability parameters (maximum plasma concentration, Cmax, and the area under the concentration-versus-time curve extrapolated to infinity, AUC0-∞) of both products. In the case of the time to maximum concentration (Tmax), non-parametric tests based on Wilcoxon's signed rank test were preferred. The comparison of the mean AUC0-∞ values did not reveal any significant differences (311.40 ± 93.05 μg h/mL and 287.71 ± 45.31 μg h/mL, respectively). The results were similar for the Tmax (3.58 ± 0.90 h versus 3.42 ± 0.51 h). However, when comparing the mean Cmax some significant differences were found (8.73 ± 3.66 μg/mL and 10.43 ± 3.84 μg/mL, respectively). The 90% confidence intervals for the ratio of AUC0-∞ and Tmax values for the reference and test product are within the interval 80-125%, but the 90% confidence intervals for the ratio of Cmax falls outside the proposed interval. It was concluded that Cmax of test product are not within the 20% of those of the reference, thus suggesting that test OTC is not bioequivalent to the reference formulation.